Direct market costs of aflatoxins in Kenyan dairy value chain - Senerwa, D.M.; Mtimet, Nadhem; Sirma, A.J.; Nzuma, J.; Kang'ethe, Erastus K.; Lindahl, Johanna F.; Grace, Delia (University of Nairobi, 2016)
Introduction Mycotoxin producing fungi contaminate feeds pre- or post harvest and produce aflatoxins B1, B2, G1 and G2. Aflatoxin B1 is a class 1 human carcinogen and is converted to aflatoxin M1 by cows and secreted in milk. Aflatoxin M1 is a class 2B (possible) carcinogen and is associated with stunting in children. Aflatoxin B1 in feeds causes a decrease in milk production, reduced feed conversion efficiency and reduced fertility. A cross-sectional study to assess the economic costs of aflatoxins was done in five counties in Kenya. Methods A map of the five agro-ecological zones of Kenya was used to select the study sites: Kisii and Bungoma (temperate), Tharaka-Nithi (humid), Kwale (sub-humid), and Isiolo(semi-arid). One sublocation was randomly selected from each county. Multistage cluster sampling was done with sub-locations, then villages, then dairy farmers (Dohoo et al., 2012). Milk samples were collected from the dairy farmers. Feed samples were collected from the dairy farmers, feed traders and feed manufacturers. Aflatoxin B1 and M1 quantification in dairy feeds and milk was done using a competitive ELISA. Possible economic costs of aflatoxins were estimated using annual quantities/market prices of feeds and milk having aflatoxin B1 or M1 respectively above the WHO/FAO standards. Findings and interpretations Sixty two of 101 (61.4%) dairy feed samples from feed manufacturers had aflatoxin B1 levels above the FAO/WHO/Kenya limit of 5 ppb. If this Kenyan legislation would be enforced, the possible economic cost per year for dairy feed manufacturers would be 22.2 billion US$. Seventeen of 118 (14.4%) dairy feed samples from farmers had aflatoxin B1 levels above 120 ppb. Aflatoxin B1 concentrations above 120 ppb in dairy feeds has been shown to cause a 25 % drop in milk production(Guthrie and Bedell, 1979). The annual cost for farmers in Kenya feeding their cows on dairy feeds with aflatoxin B1 above 120 ppb is estimated at 37.4 million US$. Of the 283 milk samples from the five counties, 10.3% had aflatoxin B1 levels above WHO/FAO limit of 50 ppt which would cost dairy farmers 113.4 million US $ per year, if legislation was enforced. Education of farmers, feed manufacturers and traders on good agricultural and feed storage practices could reduce the level of contamination and multiplication of aflatoxin producing fungi and increase profits for the dairy farmers.